CODE SWITCHING AND CODE MIXING IN THE ARABIC LEARNING OF 'EGYPT SANDWICH PROGRAM 2019' - Jamaluddin Abdul Aziz; Mohamad Zaka Al Farisi; Muhammad Zainal Muttaqien (Leksema: Jurnal Bahasa dan Sastra, 2021)
This study discusses the types of code switching and code mixing occured in the utterances of Egypt Sandwich Program 2019instructors. It also explores the factors that cause the two language phenomena and their effects toward non-Arabic speakers. In research design, participatory observational study was applied in which the researchers participated in the Arabic language learning activities in the program. The results showed that both internal and external code switching occurred in the speech of the instructors. Meanwhile, for code mixing, intersentential and intrasentential process were found in this study. The code switching and code mixing found in this study only occured among Arabic fusha, Arabic ‘amiyah, and English. In general, the main factor that drove the speakers to perform code switching and code mixing in the program was the speaker’s habitl. Misunderstandings sometimes happened between the instructors and the students due to the emergence of code switching and code mixing in the event.